Mycobacterium marinum Escapes from Phagosomes and Is Propelled by Actin-based Motility - Stamm, Luisa M. (The Rockefeller University Press, 2003)
Mycobacteria are responsible for a number of human and animal diseases and are classical intracellular pathogens, living inside macrophages rather than as free-living organisms during infection. Numerous intracellular pathogens, including Listeria monocytogenes, Shigella flexneri, and Rickettsia rickettsii, exploit the host cytoskeleton by using actin-based motility for cell to cell spread during infection. Here we show that Mycobacterium marinum, a natural pathogen of fish and frogs and an occasional pathogen of humans, is capable of actively inducing actin polymerization within macrophages. M. marinum that polymerized actin were free in the cytoplasm and propelled by actin-based motility into adjacent cells. Immunofluorescence demonstrated the presence of host cytoskeletal proteins, including the Arp2/3 complex and vasodilator-stimulated phosphoprotein, throughout the actin tails. In contrast, Wiskott-Aldrich syndrome protein localized exclusively at the actin-polymerizing pole of M. marinum. These findings show that M. marinum can escape into the cytoplasm of infected macrophages, where it can recruit host cell cytoskeletal factors to induce actin polymerization leading to direct cell to cell spread.